Study of central exclusive W+W− in the fully leptonic channel at √s =13 TeV with PPS/CMS and investigation of anomalous quartic gauge couplings - Chagas, Ewerton Belchior Batista das (2019)
In this thesis we present a study on the central exclusive process γγ → W+W− in the fully leptonic channel with PPS/CMS in the center of mass energy √s = 13 TeV and an investigation of anomalous quartic gauge couplings (AQGC s). Central exclusive processes pp → p ⊕ X ⊕ p are characterised by rapidity gaps between the central system X and the scattered protons. The muon channel is characterised by a missing transverse energy (MET) associated to the neutrinos, and the proton tagging is done using the new forward detector PPS (CMS-TOTEM Precision Proton Spectrometer), located at about ±210 ~ m from the interaction point. We present a proposal of a kinematic fit for the discrimination between the signal and associated background, which allows one to match the central system X with the kinematics of the protons reconstructed at PPS. Different values of couplings are studied aiming to obtain a better understanding on the achievable sensitivity when considering the fully leptonic final state.